The MPEG handbook : MPEG-1, MPEG-2, MPEG-4 - Watkinson, John, 1950- (Elsevier/Focal Press, 2004)
A complete, professional 'bible' on all aspects of audio and video compression using MPEG technology, including the MPEG-4 standard and, in this second edition, H-264. The clarity of explanation and depth of technical detail combine to make this book an essential and definitive reference work. THE MPEG HANDBOOK is both a theoretical and practical treatment of the subject. Fundamental knowledge is provided alongside practical guidance on how to avoid pitfalls and poor quality. The often-neglected issues of reconstructing the signal timebase at the decoder and of synchronizing the signals in a multiplex are treated fully here. Previously titled MPEG-2, the book is frequently revised to cover the latest applications of the technology. * Benefit from John Watkinson's in-depth understanding of MPEG technology with explanations developed and proven in seminars presented worldwide. * Comprehensive coverage of the main and latest standards--MPEG-1, MPEG-2, MPEG-4, H-264. * Learn how you can apply MPEG technology to achieve the best quality. * Coverage of enabling technologies such as interpolation, motion estimation and transforms. * An invaluable treatment of significant new extensions made available by MPEG-4, such as object coding, mesh coding and animation. * Essential reading for those involved with the delivery of compressed audio, video, graphics and interactive capability over the Internet and broadband networks.